Determinants of Corporate Social Responsibility disclosure in State-owned Enterprises: Moderating role of government regulation and organizational slack - Wilsna Rupilu; Eugenia Hendrini P. Tanan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aimed to examine the effects of Green Accounting, Good Corporate Governance (GCG), Financial Performance, and Leverage on Corporate Social Responsibility (CSR) Disclosure, with Government Regulation and Organizational Slack as moderating variables in State-Owned Enterprises (SOEs).Method — This research was quantitative, employing hypotheses and statistical tools for analysis. The population in this research is limited to manufacturing companies, specifically in the mining, energy, and oil and gas sectors of State-Owned Enterprises listed on the Indonesia Stock Exchange. The sample size consisted of 40 companies with an observation period from 2018 to 2022. The research process began with descriptive statistical analysis, classical assumption tests, and hypothesis testing. Hypothesis testing in this study involved multiple regression analysis to incorporate moderating variables (MRA).Result — The results of the study indicated that Green Accounting, Good Corporate Governance, Financial Performance, and leverage variables had an impact on Corporate Social Responsibility, while government regulation and organizational slack did not moderate the relationship between Green Accounting, Good Corporate Governance, Financial Performance, and leverage with Corporate Social Responsibility.Contribution — This study stands out with its unique approach. It focuses on state-owned companies in mining, energy, and oil and gas over five years (2018-2022), including the COVID-19 period, shedding light on its impact on CSR reporting. The study also uses new variables, giving us fresh insights into CSR practices in these industries. In summary, it provides valuable new information about CSR in state-owned enterprises in these sectors.